Harmonic Numbers and Cubed Binomial Coefficients - Sofo, Anthony (International Journal of Combinatorics, 2011)
Euler related results on the sum of the ratio of harmonic numbersand cubed binomial coefficients are investigated in this paper. Integraland closed-form representation of sums are developed in terms of zeta andpolygamma functions. The given representations are new.